Penggunaan Media Pembelajaran Flashcard dalam meningkatkan Hasil Belajar Peserta Didik pada Materi Skala Kelas VI SDN Burengan 02 Kediri - Aprilianti, Wiwit; Mukmin, Bagus Amirul; Putra, Aji Setya Gaya (Cipta Media Harmoni, 2025)
This research was conducted to address the urgent issue of low mathematics learning outcomes for sixth-grade students at SDN Burengan 02 Kediri, particularly in understanding the concept of scale, especially in comparing sizes in images with actual sizes. The objective of this research is to improve students' learning outcomes through the use of learning media in the form of flashcards. The method in this research applies the Kemmis and McTaggart design to conduct Classroom Action Research (CAR) with four stages in each cycle: planning, action implementation, observation, and reflection. The results of the study indicate that the use of flashcards as a learning medium is capable of improving students' learning outcomes. In the pre-cycle phase, the average student score was 72.3 with a completeness level of 32.26%. In cycle I, after the action of applying flashcards in the learning process, the average score increased to 76.5 with a completeness rate of 54.84%. In cycle II, the scores further increased to 81.1 with a completeness of 87.10%. From these findings, it can be concluded that flashcard media is efficient in improving students' understanding of the concept of scale.